(untitled) - Hamlin, J. Scott (San Francisco, Calif., 2003)
You don't have to be a programmer to achieve amazing effects with the hundreds of Flash components available from Macromedia and various third parties. Step by step, The Hidden Power of Flash Components shows you how--and the enclosed CD provides a library of powerful components ready for you to practice with, build upon, and use in your own projects. For those of you with just a little programming experience, this book also demonstrates how to build your own components to use and share with other developers. Whatever your aims, and regardless of your experience, soon all the power of this incredible Flash feature will be within your reach.
Keywords: Flash (Computer file),Computer animation,Web sites; Design